Pengaruh Deskriptor Pembelian Terhadap Kebahagiaan Konsumen - Muhammad Ilham; Mahjudin Mahjudin; Dody Suhermawan; Enny Istanti (Journal of Management and Creative Business, 2023)
The research highlights the results of a multivariable study on the influence of purchase descriptors on consumer happiness. Using a well-established consumer decision-making paradigm, participants were randomly assigned to hypothetical scenarios in which purchase descriptors were experimentally manipulated. The variables consumer happiness, subjective well-being, consumer choice, and additional consumer attitudes were used as outcome variables. There is evidence that participants varied in terms of consumer happiness based on the specific purchase description conditions they were assigned. This research contributes to the scientific literature on consumer decision making by adding clarity to the role of important purchase-related variables on consumer happiness.